Etika Protes dalam Perspektif Hadis - Nurnazilatul Wahdah; Repa Hudan Lisalam (Moral : Jurnal kajian Pendidikan Islam, 2025)
A discussion on Islamic morality and ethics is the purpose of this paper. We see many modern generations paying little attention to how to apply morality in their daily lives. Morals and ethics are human behaviours in daily life that have been instilled. Morals come from the Qur'an and the Hadith of the Prophet Muhammad and include what is good, bad, right, and wrong in one's actions. Meanwhile, ethics come from the culture and customs of the local community. In this paper, the author discusses the meaning of morals and ethics, human relationships with God, humans, and nature. Protest is a legitimate form of expression in a democratic society. In Islam, protest is also recognised as the right of everyone to voice injustice and bias. However, protests must also be carried out with ethics that are in accordance with Islamic teachings. The ethics of protest can be explained in the hadith, namely: Protests must be carried out peacefully and not violate the law. This is in accordance with the hadith of the Prophet Muhammad SAW, "Whoever sees an evil should change it with his hand. If he is unable, then with his tongue. If he is unable, then with his heart. And that is the weakest faith." (HR Muslim). In this Hadith, the Prophet Muhammad (PBUH) teaches that protests should be done in stages, starting with the lightest action, namely giving a direct response. If you are unable to do so, then you can protest verbally, for example by expressing your opinion or criticism through the media. If that is no longer possible, then protest can be done in the heart, i.e. still rejecting evil, but not taking actions that can lead to violence or riots. Protest must be based on truth and justice. This is in accordance with the hadith of the Prophet Muhammad (saw), "Indeed, Allah is true and loves truth." (Narrated by Bukhari) In this hadith, the Prophet Muhammad (saw) affirms that protest must be based on truth and justice. This means that protest must be done because of real injustice, not because of personal or group interests.